2005
DOI: 10.1098/rsif.2005.0096
|View full text |Cite
|
Sign up to set email alerts
|

Extending the dynamic range of phase contrast magnetic resonance velocity imaging using advanced higher-dimensional phase unwrapping algorithms

Abstract: Phase contrast magnetic resonance velocity imaging is a powerful technique for quantitative in vivo blood flow measurement. Current practice normally involves restricting the sensitivity of the technique so as to avoid the problem of the measured phase being 'wrapped' onto the range -pi to +pi. However, as a result, dynamic range and signal-to-noise ratio are sacrificed. Alternatively, the true phase values can be estimated by a phase unwrapping process which consists of adding integral multiples of 2pi to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 16 publications
1
41
0
Order By: Relevance
“…As the edge of any surface is closed loop, the residues along a discontinuity surface edge also form a closed loop. Furthermore, it can be shown that all residues, including those within discontinuity surfaces, form loops in 3D space [12,16]. These loops are referred to in previous publications as "phase singularity loops" [12,16], but we use the term "residue loop" to be consistent with our use of the term "residue" to describe phase singularities.…”
Section: Theory Of Three-dimensional Unwrappingmentioning
confidence: 77%
See 3 more Smart Citations
“…As the edge of any surface is closed loop, the residues along a discontinuity surface edge also form a closed loop. Furthermore, it can be shown that all residues, including those within discontinuity surfaces, form loops in 3D space [12,16]. These loops are referred to in previous publications as "phase singularity loops" [12,16], but we use the term "residue loop" to be consistent with our use of the term "residue" to describe phase singularities.…”
Section: Theory Of Three-dimensional Unwrappingmentioning
confidence: 77%
“…Although we expect these surfaces to be rare in well-sampled data sets, fitting a minimal surface to every loop does not allow for this type of surface, hence we refer to it as a quasi-L ϱ approach. Existing branch-cut algorithms [12,[14][15][16]] also fall in this class, although the ways in which truncated residue loops are handled by these algorithms do not minimize the L ϱ -norm for the general case. In the following section we describe an algorithm to implement the quasi-L ϱ approach that applies for all residue loops, including those that are truncated.…”
Section: B Multiple-cycle Discontinuity Surfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…The existing PU algorithms can be grouped into three major categories: 1) path-following algorithms [3] [5] [6]; 2) one-dimensional PU [7] [8]; and 3) minimum norm algorithms [2] [9] [10]. The algorithm proposed in this paper falls in the third category.…”
Section: Introductionmentioning
confidence: 99%